FLOOD VULNERABILITY LEVEL STUDY BASED ON LAND BIOPHYSICAL ASPECTS IN THE KRUENG JREUE SUB-DAS, ACEH BESAR - Eka Sri Wulandari; Helmi (Jurnal Penelitian Progresif, 2024)
The increasing intensity of land conversion in the Krueng Jreue Aceh Besar Sub-watershed due to changes in land use causes changes in the biophysical characteristics of the land. Changes in the biophysical characteristics of land cause an increase in the level of flood vulnerability. This research uses a descriptive method (survey). The research results show: Variables determining the level of flood vulnerability are based on biophysical aspects of the land, namely: dynamic factors (rainfall, land use), and static factors (soil infiltration, slope slope).Flood Vulnerability Level Classes (TKB) in the Krueng Jreue Sub-watershed consist of: Very Vulnerable, settlements and rice fields (42≤TKB≤50); Vulnerable, moor (34≤TKB≤41); Moderately Vulnerable/Moderate open land, bushes, grasslands, secondary forests and primary forests (26≤TKB≤33); mean 32.38 (moderately vulnerable class).Residential land and rice fields in the cultivation area, covering an area of ​​624.76 ha or 2.70% of the total area of ​​the Krueng Jreue Sub-watershed (23,218.06 ha), have the highest level of vulnerability to flood disasters. Flood disasters occur in November-December, when rainfall is high.